Advances in application of hypoxia-preconditioned mesenchymal stem cell-derived exosomes - Zhuo, Haitao; Chen, Yunfei; Zhao, Guifang (Frontiers in Cell and Developmental Biology, 2024)
Mesenchymal stem cells (MSCs) primarily secrete physiologically functional exosomes via paracrine effects that act on various adjacent and distant cells, thus exerting their therapeutic effects. In recent years, hypoxic preconditioning, as a novel MSC culture mode, has emerged as a research hotspot. Many previous studies have shown the role and underlying regulatory mechanisms of hypoxic preconditioning in various diseases, which has provided sufficient reference materials for the MSC research field. Therefore, this review summarizes the progress in application of hypoxia-preconditioned MSC-derived exosomes that substantially increases and improves the biological activity of specific molecules, such as microRNA.